2015
DOI: 10.1017/s0025315415001575
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of silky shark Carcharhinus falciformis in the eastern Arabian Sea

Abstract: Reproduction, diet and growth of silky shark Carcharhinus falciformis in the eastern Arabian Sea are described based on 473 specimens collected from the gillnet-cum-longline landings at the Cochin fisheries harbour during 2012–2014. The reproductive biology of 215 males and 258 females was examined while 113 stomachs were sampled to study the diet. The von Bertalanffy growth parameters estimated using length-based models were asymptotic length (L∞) = 309.80 cm, growth coefficient (K) = 0.10 year−1 and age at z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…However, the size range of this study closely resembles to what was reported in the Central-Western Pacific in 2014 (65-271 cm TL) [9]. The sexual proportion was skewed towards females, which coincides with what was reported by Hoyos-Padilla et al [61] and Varghese et al [62]. However, it differs from other studies [15,63,64], where they found no difference in abundance between females and males.…”
Section: Carcharhinus Falciformissupporting
confidence: 89%
See 2 more Smart Citations
“…However, the size range of this study closely resembles to what was reported in the Central-Western Pacific in 2014 (65-271 cm TL) [9]. The sexual proportion was skewed towards females, which coincides with what was reported by Hoyos-Padilla et al [61] and Varghese et al [62]. However, it differs from other studies [15,63,64], where they found no difference in abundance between females and males.…”
Section: Carcharhinus Falciformissupporting
confidence: 89%
“…The maturity size for males was 182.10 cm TL, which was very similar to that recorded in the Central-Western Pacific (183 cm TL) [9], in the Mexican South Pacific (180 cm TL) [63] and on the West Coast of Baja California Sur (182 cm TL) [61]. However, the maturity size seems to be bigger in the Eastern Indian Ocean (207.6 cm TL) [64], in the Eastern Arabian Sea (218.98 cm TL) [62] and in Campeche Bank (225 cm TL) [60]. These results suggest that males of Carcharhinus falciformis reach sexual maturity at a smaller size in the Pacific.…”
Section: Carcharhinus Falciformissupporting
confidence: 80%
See 1 more Smart Citation
“…In conclusion, elasmobranchs, including shark-like batoids have low resilience to overexploitation by fisheries because of their atypical life history traits including late attainment of maturity, low fecundity and natural mortality, slow growth, long life spans and the close relationship between the number of young ones produced and the size of breeding biomass (Stevens et al, 2000;Varghese et al, 2016). The restricted coastal habitat, limited life history characteristics, susceptibility to capture in multiple gears and ever growing demand place coastal rhynchobatids amongst the most vulnerable chondrichthyan fishes (Dudley and Cavanagh, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the life‐history traits and habitat characteristics are highly important in ensuring sustainable fisheries and informing management decisions. The life‐history patterns of chondrichthyans of Indian waters are poorly understood (Akhilesh et al ., ; Kizhakudan et al ., ), but recently there have been concentrated efforts to fill this knowledge gap (Raje et al ., ; Varghese et al ., ) and more regulatory (conservation and trade) implications in the region ( e.g . finning ban and fin attached policy, fin export ban).…”
Section: Stomach‐content Prey Items By Number (%N) Mass (%M) Occurrmentioning
confidence: 99%